Ponseti Technique for the Management of Congenital Talipes Equinovarus in a Rural Set-Up in India: Experience of 356 Patients - Rohit Malhotra; Ashutosh Mohapatra; Geetika Arora; Priyam Choudhury; Hitesh Joshi; Pranav Patel (MDPI AG, 2018)
Congenital talipes equinovarus (CTEV), also known as clubfoot, is a complex congenital deformity of the foot that, left untreated, can limit a person's mobility by making it difficult and painful to walk. Worldwide, 80% of children born with clubfoot are in low- and middle-income countries. The management of clubfoot has a long history. Non-operative management did not become popular, as an increasing number of orthopaedists started leaning towards surgical treatment. The late Dr. Ignacio Ponseti developed a method of clubfoot correction that successfully realigns clubfoot in infants without extensive and major surgery. The aim of the study was to assess the functional outcome of CTEV management by the Ponseti technique, to study the severity of CTEV deformity using the Pirani score, and to evaluate the cost-effectiveness of the technique. A total of 356 cases with 402 feet with CTEV were treated by the Ponseti method. The average age of the children and the number of casts applied before full correction were 4.03 months and 6.91, respectively. There was a good functional outcome in 95.45% of cases (score > 30) at the last follow up. The management of CTEV by the Ponseti technique provides a good functional and cosmetic outcome. In a developing country like India, this technique is a safe, easy, economical method of clubfoot management.